Economic evaluation of delivering Haemophilus influenzae type b vaccine in routine immunization services in Kenya - Angela Oloo Akumu; Mike English; J Anthony G Scott; Ulla K Griffiths (The World Health Organization, 2007)
OBJECTIVE: Haemophilus influenzae type b (Hib) vaccine was introduced into routine immunization services in Kenya in 2001. We aimed to estimate the cost-effectiveness of Hib vaccine delivery. METHODS: A model was developed to follow the Kenyan 2004 birth cohort until death, with and without Hib vaccine. Incidence of invasive Hib disease was estimated at Kilifi District Hospital and in the surrounding demographic surveillance system in coastal Kenya. National Hib disease incidence was estimated by adjusting incidence observed by passive hospital surveillance using assumptions about access to care. Case fatality rates were also assumed dependent on access to care. A price of US$ 3.65 per dose of pentavalent diphtheria-tetanus-pertussis-hep B-Hib vaccine was used. Multivariate Monte Carlo simulations were performed in order to assess the impact on the cost-effectiveness ratios of uncertainty in parameter values. FINDINGS: The introduction of Hib vaccine reduced the estimated incidence of Hib meningitis per 100 000 children aged < 5 years from 71 to 8; of Hib non-meningitic invasive disease from 61 to 7; and of non-bacteraemic Hib pneumonia from 296 to 34. The costs per discounted disability adjusted life year (DALY) and per discounted death averted were US$ 38 (95% confidence interval, CI: 26-63) and US$ 1197 (95% CI: 814-2021) respectively. Most of the uncertainty in the results was due to uncertain access to care parameters. The break-even pentavalent vaccine price - where incremental Hib vaccination costs equal treatment costs averted from Hib disease - was US$ 1.82 per dose. CONCLUSION: Hib vaccine is a highly cost-effective intervention in Kenya. It would be cost-saving if the vaccine price was below half of its present level.